Upper limb sensorimotor recovery in Asian stroke survivors: a study protocol for the development and implementation of a Technology-Assisted dIgitaL biOmaRker (TAILOR) platform - Cheng, Hsiao-Ju; Chin, Lay Fong; Kanzler, Christoph M.; Lehner, Rea; Kuah, Christopher W. K.; Kager, Simone; Josse, Eva; Samkharadze, Tengiz; Sidarta, Ananda; Gonzalez, Pablo Cruz; Lie, Eloise; Zbytniewska-Mégret, Monika; et al. (Frontiers in Neurology, 2023)
Background: Post-stroke functional impairments have only been investigated using limited clinical scores, during short-term longitudinal studies in relatively small patient cohorts. With the addition of technology-based assessments, we propose to complement clinical assessments with more sensitive and objective measures that could more holistically inform on upper limb recovery, upper limb use in daily life, and overall quality of life after stroke. This paper describes a pragmatic, longitudinal, observational study protocol aiming to gather a uniquely rich multimodal database to comprehensively describe the time course of upper limb recovery in a cohort of 400 Asian stroke survivors. We will characterize the longitudinal relationship between upper limb recovery, common post-stroke impairments, functional independence, and quality of life. Methods: Participants with stroke will be tested at eight time points, from within a month to three years post-stroke. We will perform a battery of established clinical assessments to describe the factors most likely to influence upper limb recovery, using (1) digital health biomarkers from robotic or wearable sensing technology-assisted assessments to sensitively characterize motor and somatosensory impairments and upper limb use in daily life; (2) quantitative and qualitative measures to understand health-related quality of life; (3) transcranial magnetic stimulation to describe neurophysiological motor status. Statistics: Descriptive analyses will be performed to understand post-stroke upper limb impairments and recovery at various time points. Multiple statistical models will be constructed to characterize the time course of the recovery. Subgroups of stroke survivors exhibiting distinct recovery profiles will be identified. Conclusions: This is the first study complementing clinical assessments with technology-assisted digital biomarkers to investigate upper limb recovery in Asian stroke survivors. Overall, this study will yield a multimodal data set that longitudinally characterizes post-stroke upper limb recovery in functional impairments, daily-life upper limb use, and health-related quality of life in Asian stroke survivors. This data set generates valuable information on post-stroke upper limb recovery and potentially allows researchers to identify different recovery profiles of subgroups of Asian stroke survivors. Thus, this study builds the basis to identify early predictors for upper limb recovery, inform clinical decision-making in Asian stroke survivors and establish tailored therapy programs.